Correlation of Histopathological Changes with the Manner of Death in Fatal Burns in a Tertiary Care Hospital in Northern India (Medico Legal Update, 2019)
Objectives: To find the correlation of manner of death with histopathological changes in fatal burns in atertiary care hospital in north India.Method: This was a comparative study. Cases were thoroughly studied usingspecially designed proformathat included the demographic profile of deceased along with information gathered from relatives, police& hospital records and autopsy findings. Before taking the lung sample, proper consent was taken fromthe relatives after explaining the purpose of the study. After gross examination, sections were taken fromdifferent lobes of lungs.Results: Tracheal congestion was found mainly in accidental deaths (49.77%), followed by suicidal deathswith 28.57% and homicidal deaths with 21.66%. This difference was found to be statistically significant(p